RETRACTED: IAV Antagonizes Host Innate Immunity by Weakening the LncRNA-LRIR2-Mediated Antiviral Functions - Na Chen; Baoge Zhang (Biology)
A growing number of studies have shown that long non-coding RNAs (lncRNAs) are implicated in many biological processes, including the regulation of innate immunity and IAV replication. In addition, IAV has been found to be able to hijack lncRNAs and thus antagonize host innate immunity. Nonetheless, whether IAV can antagonize host innate immunity by weakening the antiviral functions mediated by lncRNAs is unknown. In this study, we found that LncRNA-ENST00000491430 regulates IAV replication and named it LRIR2. Interestingly, we found that the expression of LRIR2 was suppressed during IAV infection. Importantly, LRIR2 overexpression inhibited IAV replication, suggesting that LRIR2 plays an antiviral role during IAV infection. Mechanistically, we demonstrated that LRIR2 inhibits the transcription and replication of the IAV genome. In addition, the antiviral function of LRIR2 is mainly dependent on the stem-loop structures of 1–118 nt and 575–683 nt. Taken together, IAV could antagonize host innate immunity by weakening the LncRNA-LRIR2-mediated antiviral functions. Our study provides novel perspectives into viral strategies to antagonize host innate immunity. It lays a theoretical foundation for the design of novel anti-IAV drugs that target host lncRNAs or the antagonism effect.